Analisis Pengaruh Pelatihan dan Motivasi Terhadap Peningkatan Kinerja Guru di Kecamatan Wera - jeki julkarnain (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2024)
This research aims to analyze the influence of training and motivation on improving teacher performance in Wera District. The method used is quantitative with a survey approach. Data was collected through questionnaires distributed to 135 teachers in various schools in Wera District. Data analysis was carried out using multiple regression techniques to identify the relationship and influence of each independent variable, namely training and motivation, on the dependent variable, namely teacher performance. The research results show that training has no effect on teacher performance. Motivation has a significant positive influence on teacher performance.